Frontstage and backstage in Argentina’s transitional justice drama: the niet@s’ reconstruction of identity on social media - Goldschmidt-Gjerløw, Beate (International journal of transitional justice, 2019)
This article provides new insight into how the ‘found grandchildren’ of postconflict Argentina are reconstructing their sense of self and identity after having been identified as children of disappeared political activists in the aftermath of the last military regime (1976-1983). We offer tools for understanding how they respond to the context-specific transitional justice measures of identification and restitution, and how this plays out on social media. This online world expands the possibilities to both share and comment on personal and public information. The narrative analysis discusses how our informants influence the Argentine transitional justice process by using social media as a stage for the performance of their life stories. However, their digital presentation of self is constrained to a certain extent by potential social reactions.